2022
DOI: 10.1590/0037-8682-0617-2021
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in indigenous and non-indigenous patients aged under 15 years between 2007-2018, Amazonas state, Brazil

Abstract: Background: Malaria is a serious problem in children because the immune system is less developed, thus, causing more severe symptoms. This study aimed to identify factors associated with malaria in indigenous and non-indigenous patients aged under 15 years in Amazonas, Brazil, from 2007 to 2018.Methods: An epidemiological, quantitative, cross-sectional study was conducted. Cases included patients aged under 15 years, using data from health system notifications between 2007 and 2018 in the state of Amazonas, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Los factores de riesgos de malaria en el cantón Aguarico afectan especialmente a varones indígenas que viven en zonas rurales debido al contacto con personas infectadas, el no uso de toldo, hacinamiento y presencia de agua estancada cerca de las viviendas. Estos hallazgos guardan relación con lo encontrado en estudios de (Meireles et al, 2020) y (Aguiar et al, 2022) y (Caldas et al, 2023), quienes destacan la gravedad de la malaria en hombres indígenas de zonas rurales. De manera similar, otros estudios efectuados por (Workineh et al, 2021), (Duguma et al, 2022), (Padrón Echenique et al, 2021), (Cardona-Arias et al, 2019, (Woday et al, 2019), también confirman que el contacto con infectados, la falta de uso de mosquiteros, la presencia de agua estancada cerca de los hogares y el hacinamiento aumentan el riesgo de contraer malaria.…”
Section: Discussionunclassified
“…Los factores de riesgos de malaria en el cantón Aguarico afectan especialmente a varones indígenas que viven en zonas rurales debido al contacto con personas infectadas, el no uso de toldo, hacinamiento y presencia de agua estancada cerca de las viviendas. Estos hallazgos guardan relación con lo encontrado en estudios de (Meireles et al, 2020) y (Aguiar et al, 2022) y (Caldas et al, 2023), quienes destacan la gravedad de la malaria en hombres indígenas de zonas rurales. De manera similar, otros estudios efectuados por (Workineh et al, 2021), (Duguma et al, 2022), (Padrón Echenique et al, 2021), (Cardona-Arias et al, 2019, (Woday et al, 2019), también confirman que el contacto con infectados, la falta de uso de mosquiteros, la presencia de agua estancada cerca de los hogares y el hacinamiento aumentan el riesgo de contraer malaria.…”
Section: Discussionunclassified
“…Although it is challenging to pinpoint the exact transmission sites of the disease, it has been suggested that children are more susceptible to mosquito bites at night while sleeping or during daily activities. 8 Nevertheless, the favorable environment for Anopheles species mosquitoes reproduction and dissemination in water reservoirs left in the mines increases the risk of infection among miners. 4…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more than 1,600 cases have been reported in children under one year of age in the Amazon region, based on the probable location of infection. Cases in this age group are particularly associated with recurring episodes of malaria and increased clinical severity 56 , which can have a significant impact on the health and cognitive development of affected children, as well as the well-being of the community. Indigenous communities also suffer from other health problems, such as respiratory diseases, malnutrition due to mercury contamination of water/food, neurological diseases related to mercury poisoning, and violence, especially in the Yanomami indigenous territory 33 , the largest in Brazil, where the third largest area of illegal mining in indigenous lands is located 28 .…”
Section: Illegal Mining In Indigenous Areasmentioning
confidence: 99%